Clinical researchTransvaginal doppler sonography for assessment the response to radiotherapy in locally advanced squamous cervical cancer: a preliminary study - Gottwald, Leszek; Lech, Waldemar; Sobotkowski, Janusz; Spych, Michał; Pluta, Piotr; Moszyńska-Zielińska, Małgorzata; Kazmierczak-Lukaszewicz, Sylwia; Ciałkowska-Rysz, Aleksandra (Archives of Medical Science, 2009)
Introduction: The place of sonography in the diagnostics and monitoring of cervical carcinoma remains controversial. Aim of the study is to assess the value of transvaginal sonography (TVS) and transvaginal color Doppler sonography (TVCD) for assessment of the effect of treatment in patients with locally advanced squamous cervical cancer. Material and methods: Research included 18 patients with cervical cancer aged 36-72 year in FIGO stages II (11 patients) and III (7 patients) treated by ra-diotherapy. TVS and TVCD were performed: before the beginning of treatment (I), 3 days after radiotherapy (II), and 6 weeks after radiotherapy (III). The clinical course of disease in 6 months after treatment was evaluated. Results: In each patients the volume of uterine cervix decreased after radiotherapy. The median values of RI were similar in each examinations. During 6 months of observation in 5 women out of 18 patients the progression of the cervical cancer was noted. Only in 2 out of 5 cases the progression was local, and in 3 patients distant metastases were found. In retrospective analysis we did not found statistically significant differences in results of sonographic examinations I, II, and III between patients with remission and progression of cervical cancer. Conclusions: TVS is useful for estimation of uterine cervix during radiation therapy due to locally advanced cervical cancer, but its usefulness in prediction of progression of the cancer is rather low. The value of the assessment of RI in descending branches of uterine arteries in monitoring the treatment of the cervical cancer was not confirmed.